Application of Government Authority to the Application of Corporate Sanctions That Pay Less Attention to Labor Welfare In Indonesian - Rifandhana, Raditya Feda; Ningtias, Ayu Dian (Universitas Islam Lamongan, 2023)
Indonesia is a country that has a population density of 275 773.8 million people, of thetotal population density, the working population of Indonesia amounts to 8 746.01people in various fields, and their purpose of working is to fulfill a prosperous life,besides that Indonesia is a country of laws based on the Constitutions or Basic Law andLaws, so that the Law and the Basic Law (Constitutions) regulate the welfare of thepeople, The implementation of community welfare can be carried out by thegovernment which has the authority to prosper the community through the provision ofjobs through the establishment of companies in regions throughout Indonesia, theestablishment of legal companies throughout Indonesia in recruiting employees, it isnecessary to think about the welfare of both material and non-material, then thegovernment needs to make legal products, namely the Manpower Law that can meet allthe welfare of the community employee status, however, the existence of theemployment law is often ignored by the company to provide welfare for employees,and in this case there is a need for sanctions from the government to provide a deterrenteffect for companies that violate labor laws. In the idea of this research is normativejuridical research, with an